ABC of ear, nose, and throat - Ludman, Harold; Bradley, Patrick J. (ABC series (Malden, Mass.), 2013)
ABC of Ear, Nose and Throat is a long established best-selling guide to the management of common conditions of the Ears, Nose and Throat. It follows a symptomatic approach for evaluation and prioritisation of common presentations, and provides guidance on primary care assessment and management, and on when and why to refer for a specialist opinion. Fully revised to reflect the current practice of oto-rhino-laryngology and head and neck surgery, new chapters address the increasing specialization and improved understanding of the likely causes and specialist treatment for symptoms such as tinnitus, nasal discharge, nasal obstruction, facial plastic surgery, head and neck trauma and foreign bodies, and non-specialist assessment and examination. There is new content on rhinoplasty, pinnaplasty, non-melanoma skin tumours, thyroid disease and head and neck cancer, with many new full colour illustrations and algorithms throughout.